Synthesis and physicochemical characterization of bovine lactoferrin supersaturated complex with iron (III) ions - Oleksandra Pryshchepa; Katarzyna Rafińska; Adrian Gołębiowski; Mateusz Sugajski; Gulyaim Sagandykova; Piotr Madajski; Bogusław Buszewski; Paweł Pomastowski (Scientific Reports, 2022)
Abstract The aim of the study was to investigate the process of Fe3+ binding to bLTF. Moreover, the physicochemical characterization of the respective supersaturated complex was studied. The knowledge should be important for the description of processes that may take place in dairy products fortified with iron. Additionally, the synthesized complex can be utilized as a dietary supplement for the treatment of iron deficiency anemia (IDA). Finally, it was shown that formation of supersaturated iron-protein structures which include LTF often accompanies development of neurodegenerative diseases such as Alzheimer or Parkinson. Thus, the study can reveal some aspects of its pathogenesis process. The methodology of the investigation comprised the utilization of batch sorption study and applying Freundlich and Langmuir models. The complex also was characterized by numerous techniques: spectrometric (ICP-MS), spectroscopic (UV–Vis, ATR-FTIR), electron microscopy (TEM–EDX), SDS-PAGE. Based on obtained results the potential mechanisms of iron interaction with protein were described. Moreover, the molecular docking was applied to visualize possible metal binding sites. The respective complex contains ≈ 33.0 mg/g of iron which is nearly 50 Fe3+ per one protein molecule. The cytotoxicity of the obtained complex was evaluated by MTT reduction and LDH release assays on Caco-2 and nL929 cell lines.